Salp15 binding to DC-SIGN inhibits cytokine expression by impairing both nucleosome remodeling and mRNA stabilization. - Joppe W R Hovius (Public Library of Science (PLoS), 2008)
Ixodes ticks are major vectors for human pathogens, such as Borrelia burgdorferi, the causative agent of Lyme disease. Tick saliva contains immunosuppressive molecules that facilitate tick feeding and B. burgdorferi infection. We here demonstrate, to our knowledge for the first time, that the Ixodes scapularis salivary protein Salp15 inhibits adaptive immune responses by suppressing human dendritic cell (DC) functions. Salp15 inhibits both Toll-like receptor- and B. burgdorferi-induced production of pro-inflammatory cytokines by DCs and DC-induced T cell activation. Salp15 interacts with DC-SIGN on DCs, which results in activation of the serine/threonine kinase Raf-1. Strikingly, Raf-1 activation by Salp15 leads to mitogen-activated protein kinase kinase (MEK)-dependent decrease of IL-6 and TNF-alpha mRNA stability and impaired nucleosome remodeling at the IL-12p35 promoter. These data demonstrate that Salp15 binding to DC-SIGN triggers a novel Raf-1/MEK-dependent signaling pathway acting at both cytokine transcriptional and post-transcriptional level to modulate Toll-like receptor-induced DC activation, which might be instrumental to tick feeding and B. burgdorferi infection, and an important factor in the pathogenesis of Lyme disease. Insight into the molecular mechanism of immunosuppression by tick salivary proteins might provide innovative strategies to combat Lyme disease and could lead to the development of novel anti-inflammatory or immunosuppressive agents.